Coverage plants as a strategy for improving soil fertility (Research, Society and Development, 2023)
Maintaining crop productivity and the physical-chemical and biological quality of the soil constitutes one of the main challenges for the agricultural sector in establishing sustainable production. In general, the use of legumes and grasses as plants and cover crops is observed due to their properties. Therefore, the objective of the work was to evaluate different cover plants in aspects related to biomass production and the accumulation of nutrients in biomass. For this, the study was carried out in the municipality of Machado, in an experiment in randomized blocks, with 5 treatments (Brachiaria, sunn hemp, niger, Crambé and control) and four repetitions. After flowering, data regarding the parameters of green and dry biomass production and nutrient accumulation were collected, with the results being subjected to analysis of variance and the Scott-Knott mean test at 5% probability. Sunn hemp was the plant that showed the highest accumulation of nutrients in dry biomass, highlighting nitrogen (40.95 kg/ha), phosphorus (11.02 kg/ha) and potassium (60.72 kg/ha), essential elements for the development and productivity of crops. This plant was also superior to the others in terms of dry (1.75 ton/ha) and green (5.3 ton/ha) biomass production. It is concluded, therefore, that C. juncea allows the contribution of biomass in quantity and quality to optimize the physical-chemical and biological quality of the soil, being a green manure indicated for promoting more sustainable agriculture.